Core Principles & Values of Effective Team-Based Health Care - Pamela Mitchell (2022)
This paper is the product of individuals who worked to identify basic principles and expectations for the coordinated contributions of various participants in the care process. It is intended to provide common reference points to guide coordinated collaboration among health professionals, patients, and families—ultimately helping to accelerate interprofessional team-based care. The authors are participants drawn from the Best Practices Innovation Collaborative of the Institute of Medicine (IOM) Roundtable on Value & Science-Driven Health Care. The Collaborative is inclusive—without walls—and its participants are drawn from professional organizations representing clinicians on the front lines of health care delivery; members of government agencies that are either actively involved in patient care or with programs and policies centrally concerned with the identification and application of best clinical services; and others involved in the evolution of the health care workforce and the health professions